Using hormones to manage dairy cow fertility: the clinical and ethical beliefs of veterinary practitioners - Higgins, Helen M.; Ferguson, Eamonn; Smith, Robert F.; Green, Martin J. (Public Library of Science, 2013)
In the face of a steady decline in dairy cow fertility over several decades, using hormones to assist reproduction has become common. In the European Union, hormones are prescription-only medicines, giving veterinary practitioners a central role in their deployment. This study explored the clinical and ethical beliefs of practitioners, and provides data on their current prescribing practices. During 2011, 93 practitioners working in England completed a questionnaire (95% response rate). Of the 714 non-organic farms they attended, only 4 farms (0.6%) never used hormones to assist the insemination of lactating dairy cows. Practitioners agreed (.80%) that hormones improve fertility and farm businesses profitability. They also agreed(.80%) that if farmers are able to tackle management issues contributing to poor oestrus expression, then over a five year period these outcomes would both improve, relative to using hormones instead. If management issues are addressed instead of prescribing hormones, practitioners envisaged a less favourable outcome for veterinary practices profitability (p,0.01), but an improvement in genetic selection for fertility (p,0.01) and overall cow welfare (p,0.01). On farms making no efforts to address underlying management problems, long-term routine use at the start of breeding for timing artificial insemination or inducing oestrus was judged ‘‘unacceptable’’ by 69% and 48% of practitioners, respectively. In contrast, practitioners agreed ($90%) that both these types of use are acceptable, provided a period of time has been allowed to elapse during which the cow is observed for natural oestrus. Issues discussed include: weighing quality versus length of cow life, fiscal factors, legal obligations, and balancing the interests of all stakeholders, including the increasing societal demand for food. This research fosters debate and critical appraisal, contributes to veterinary ethics, and encourages the pro-active development of professional codes of conduct.